A rare co-occurrence of facial talon’s cusp on fused maxillary permanent central and lateral incisor - S Pillai, Devika; G Babu, Subhas; Lorina Castelino, Renita; Ram G, Sachin; Bhat, Supriya; Rao, Kumuda (Annals of Medical Research, 2021)
None
Keywords: Facial; Fusion; Talon; Cusp.